Physical activity behaviours in school-going adolescents in the Western Cape Province, South Africa - Naidoo, Nasheen (Department of Public Health and Family Medicine, 2015)
The aims of this study were (a) to determine the prevalence of self-reported physical activity behaviours among adolescents in Grades 8-11 in Western Cape public schools from the YRBS 2, (b) to determine if there were statistically significant differences in these behaviours in comparison to the YRBS 1 and (c) to identify the characteristics of physically inactive participants. The study design was a cross sectional national prevalence school-based quantitative survey and focused on the results from Grade 8-11 classes in public secondary schools sampled in the Western Cape Province only. A total of 1134 students were surveyed across 22 schools.